Discoursive construction of resilience as a moderate variable of emotional competence. - Veiga-Branco, Augusta (2011)
To contribute to the Resilience understanding, as an integrating construct (Zautra et al., 2008) and a dynamic process of effective adaptation in the face of adversity (Luthar, 2006), in this study, we identify two Resilience profiles: Positive and Negative, respectively, that comprising the Major and Minor Emotional Competence Profile, in previous study (Veiga-Branco, 2007). Aim: To identify attitudes that build different Resilience. Method: Qualitative and retrospective study – second of a joint study (quantitative/qualitative) on "Emotional Competence Profile" - developing a "ground theory", from the speeches of semi-structured, in-depth interviews, - using a Guide with 25 questions built for this purpose – made to an intentional sample (Glaser and Strauss, 1967) of 18 individuals: 10 men and 8 women, 29 to 53 years old, teachers in primary and secondary schools in northern Portugal, with 5 to 10 years in the profession. This sample was selected from the minimum and maximum scores found in responses to the "Emotional Competence Veiga Scale" (Veiga-Branco, 2004) in the previous quantitative study. Results: The discoursive content of the interviews, displays two Resilience Profiles: 1. "Positive Resilient - Determination and Tenderness" – personal determination built on the experiences of suffering, as a legacy of dignity and strength, which enhances feelings of self-esteem, self-confidence and selfconcept of positive dispositional attribution, without anger or self-pity. This falls in the "Greater Emotional Competence Profile" experienced: the implementation of its strategies, illustrates very effective operational routes. 2. "Negative Resilient - Affectivity and Deprivation" - it emerges from hurtful walks of life and great suffering, but - as opposed to the first - with feelings of negative emotional tone (self-pity, emotional deprivation and relational dependence) and it generates categories which insert the "Minor Emotional Competence Profile" because the strategies (personal and contextual) of emotional management seems operative, but not effective enough.